Therapeutic intracellular delivery using magnetic fields, nanoparticle technology and enhanced cell penetrating peptides - Blokpoel Ferreras, Lia Andrea (2019)
The aim of this project was to develop a platform technology for the delivery of Magnetic Nanoparticles (MNPs). The delivery system is based on the incorporation of newly formulated multi domain delivery peptides termed GET (Glycosaminoglycan Enhanced Transduction) to biocompatible dextran coated iron oxide nanoparticles. GET synergistically combines a cell penetrating domain with a heparan sulphate binding unit and it has been previously demonstrated to efficiently deliver a wide range of cargoes without the disadvantages of a cell penetrating peptide such as cytotoxicity or low functionality of the delivered cargo. This technology was initially optimised for the delivery of MNPs as a theranostic complex with application to in vivo relevant environments and then tailored for magnetically mediated gene transfer for its application on modified cell therapies. Significant advancement has been made in the last couple of years in the development of MNP based therapies. Their applications rely on their physicochemical and magnetic properties and range from drug delivery systems for targeting therapeutics, to contrast agents for Magnetic Resonance Imaging (MRI), including their use in hyperthermia, cell and protein sorting or direct iron delivery. The most frequent application of MNPs in the clinic is in MRI with several MNP formulations already approved by the Food and Drug Administration (FDA). MNPs as gene delivery vectors allow for targeted gene transfer to a specific area by means of an external magnetic field (magnetofection). Although the potential of MNPs as drug/gene targeting agents has been consistently reported in vitro, their performance in preclinical studies has not been as successful. The main challenges that have prevented the incorporation of MNPs as targeted delivery systems include on the one hand, the alteration of the physicochemical properties of MNPs when they enter in contact with biological environments which makes it difficult to predict their behaviour in vivo. On the other hand, the lack of systems capable to generate a precise magnetic field capable to concentrate particles on a specific area against blood flow has restricted successful uptake in the targeted area in vivo. Since magnetic force is a function of the distance between the particle and the source of the magnetic field, this task becomes more complex the deeper the organ is inside the body. Asides from improving biomedical magnetic field settings, current efforts are focused on the formulation of stable (resistant to modification by interaction with biological matrixes) and long circulating MNPs that favour the fast cellular uptake at the target site, in order to reduce the need of long retention times at the target site. GET was able to safely mediate sustained intracellular transduction of MNPs even in the presence of plasma proteins. In order to exploit the ability of GET to promote the intracellular transduction of MNPs for gene delivery purposes, a modified version, able to efficiently condense DNA was conjugated with MNPs to develop a magnetic gene delivery vector. GET-MNPs mediated magnetofection significantly improved gene transfer speed achieving transfection efficiencies compared to commercially standard reagents in 1 hour. Additionally, external manipulation of the MNPs after delivery by the application of an external magnetic field, further enhanced transfection efficiency. Overall the two formulations of GET-MNPs were able to efficiently and safely deliver their cargo in vitro. With further development GET-MNPs could provide a flexible and tuneable platform technology for MNPs therapeutic delivery in vivo.